2000
DOI: 10.1016/s0370-2693(00)00754-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved B→πlνl form factors from the lattice

Abstract: We present the results of a lattice computation of the form factors for B 0 → π − l + ν l decays near zero-recoil. These results will allow a determination of the CKM matrix element |V ub | when measurements of the differential decay rate become available. We also provide models for extrapolation of the form factors and rate to the full recoil range. Our computation is performed in the quenched approximation to QCD on a 24 3 × 48 lattice at β = 6.2, using a non-perturbatively O(a)-improved action. The masses o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 31 publications
5
47
0
Order By: Relevance
“…Two unquenched results agree with each other within errors. These are also consistent with previous quenched calculations [43,44,45,46,47]; at present it is difficult to estimate the effect of the quenching quantitatively because the size of other systematic uncertainties O(10%) is the same as the expected size of the quenching error.…”
Section: B → πLν Decaysupporting
confidence: 89%
“…Two unquenched results agree with each other within errors. These are also consistent with previous quenched calculations [43,44,45,46,47]; at present it is difficult to estimate the effect of the quenching quantitatively because the size of other systematic uncertainties O(10%) is the same as the expected size of the quenching error.…”
Section: B → πLν Decaysupporting
confidence: 89%
“…A collection of the available results for Γ(q 2 > 16GeV 2 )/|V ub | 2 [55]- [60] is provided in fig. 6, where the band corresponds to the average…”
Section: B-physics Lattice Inputs For the Utamentioning
confidence: 99%
“…We consider partially quenched QCD with N sea sea quarks degenerate in mass (m sea ), and with two valence quarks q a and q b of masses m a and m b , respectively. Partial quenching is introduced by adding bosonic "ghost"-quarksq a,b of spin 1 2 and mass m a,b , which cancel the fermion loops of valence quarks [2,3,4,8]. Assuming the spontaneous symmetry breaking pattern to be the same as in full QCD [10], the leading-order Lagrangian for the (pseudo) Goldstone bosons is [8,9,10] …”
Section: Partially Quenched Chiral Perturbation Theorymentioning
confidence: 99%
“…It has been found that the quenching errors on the B → π and B → K transition form factors may be uncomfortably large (typically larger than 20%). This conclusion somewhat spoils the significance of the impressive agreement that has been reached amongst various lattice groups using different lattice techniques to compute B → π decay in the quenched approximation [1]. It is therefore highly important to perform the simulations in which the effects of dynamical quarks are included.…”
Section: Introductionmentioning
confidence: 99%